Prediabetes: Adherence to Nutrition Visits Decreases HbA1c in Children and Adolescents - Parajuli, Sadichchha; Jasmin, Gabrielle; Sirak, Hannan; Lee, Austin F.; Nwosu, Benjamin Udoka (Frontiers in Endocrinology, 2022)
Background: Prediabetes, the precursor of type 2 diabetes (T2D), is on the rise in the US, but the determinants of its progression are poorly characterized in youth. Objective: To determine the impact of nutrition visits, as a surrogate marker of lifestyle modification, on the trajectory of prediabetes over a 4-year period. Hypothesis: Adherence to nutrition visits could reduce BMI and lower HbA1c. Methods: A 4-year retrospective study of 108 youth with prediabetes who were recommended to receive medical nutrition therapy every 3 months following their diagnosis. Subjects were divided into 2 groups: the non-adherent group who had ≤1 nutrition visit/year, and the adherent group with ≥2 nutrition visits/year. Results: There were 46 male subjects, mean age 12.4±3.6y; and 62 female subjects, mean age, 13.3±3.0y, p=0.2. The adherent group (n=44, 41.5%) had higher BMI z-scores, but similar values for HbA1c, metformin use, and racial/ethnic composition to the non-adherent group. Overall, 18(17.0%) subjects progressed to T2D in 4y and consisted of 14(22.6%) of the 62 non-adherent subjects and 4(9.1%) of the 44 adherent subjects. The non-adherent subjects progressed to T2D at a mean duration of 25.8±12.6 months while the adherent subjects progressed at a mean duration of 34.9±11.8 months. The hazard ratio of progression from prediabetes to T2D for the non-adherent versus adherent group was 3.88 (95%CI 1.26-11.98, p=0.02). The results remained significant after adjusting for age, sex, race/ethnicity, BMI, and metformin use. Conclusion: Adherence to nutrition visits was associated with a 4-fold reduction in the likelihood to progress from prediabetes to T2D in US youth.